Partnerships for active elementary schools: Physical education outcomes after 4 months of a 2-year pilot study. (November 2017) - Weaver, R. Glenn; Webster, Collin; Egan, Catherine; Campos, Carolina; Michael, Robert D; Crimarco, Anthony
Objective: This study assessed the impact of Partnerships for Active Children in Elementary Schools (PACES) on children's moderate-to-vigorous physical activity (MVPA) during physical education (PE) and teachers' incorporation of physical activity promotion strategies after one academic semester (i.e. 4 months) of the intervention. Design: Single group pre–post pilot study. Setting: Three elementary schools in one southeastern metropolitan city in the USA. Methods: Using principles of community-based participatory-research, researchers worked with teachers to identify contextually appropriate physical activity promotion strategies aligned with prevailing recommendations, principles and theories. Outcome measures included accelerometer-derived percent of time children ( N = 150) engaged in MVPA. The System for Observing Fitness Instruction Time+ assessed changes in teachers' incorporation of physical activity promotion strategies. Multi-level mixed-effects linear regression estimated differences over time. Results: MVPA increased for girls (22.7%–26.6%) and boys (33.2%–39.0%). Small-sided games (1.0%–9.0%) and teachers' verbal promotion of physical activity (6.4%–13.5%) increased while student's off-task behaviour (6.0%–2.0%) decreased. Lines (20.2%–8.4%) and elimination games (21.6%–13.3%) decreased, but these changes were not statistically significant. Conclusion: PACES shows promise for increasing the percent of time children spend in MVPA during PE but requires further evaluation.